2020
DOI: 10.1016/j.cjtee.2020.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Global gene expression profiling of blast lung injury of goats exposed to shock wave

Abstract: Purpose Blast lung injury (BLI) is the most common damage resulted from explosion-derived shock wave in military, terrorism and industrial accidents. However, the molecular mechanisms underlying BLI induced by shock wave are still unclear. Methods In this study, a goat BLI model was established by a fuel air explosive power. The key genes involved in were identified. The goats of the experimental group were fixed on the edge of the explosion cloud, while the goats of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 48 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…Food & Function mediating the production of pro-inflammatory cytokines. 49,50 Our results indicated that CPPS treatment could inhibit ERK, p38, and p65 phosphorylation in the E. coli-infected macrophages from mice (Fig. 2E and F).…”
Section: Papermentioning
confidence: 61%
“…Food & Function mediating the production of pro-inflammatory cytokines. 49,50 Our results indicated that CPPS treatment could inhibit ERK, p38, and p65 phosphorylation in the E. coli-infected macrophages from mice (Fig. 2E and F).…”
Section: Papermentioning
confidence: 61%
“…Third, only small animals (rats) were used for in vivo evaluation. Since small and large animals have different anatomical structures and body shapes [ 54 ], further exploration of this material using large animal experiments is needed.…”
Section: Resultsmentioning
confidence: 99%
“… 9 The detailed method of BLI model was referenced from previously published papers by our research team. 10 , 11 …”
Section: Methodsmentioning
confidence: 99%